Morphine alters the circulating proteolytic profile in mice: functional consequences on cellular migration and invasion. Issue 12 (7th August 2017) - Xie, Nan; Khabbazi, Samira; Nassar, Zeyad D.; Gregory, Kye; Vithanage, Tharindu; Anand‐Apte, Bela; Cabot, Peter J.; Sturgess, David; Shaw, Paul N.; Parat, Marie‐Odile
ABSTRACT: Opioids modulate the tumor microenvironment with potential functional consequences for tumor growth and metastasis. We evaluated the effects of morphine administration on the circulating proteolytic profile of tumor‐free mice. Serum from morphine‐treated (1 or 10 mg/kg, i.p. every 12 h) or saline‐treated mice was collected at different time points and tested ex vivo in endothelial, lymphatic endothelial, and breast cancer cell migration assays. Serum from mice that were treated with 10 mg/kg morphine for 3 d displayed reduced chemotactic potential for endothelial and breast cancer cells, and elicited reduced cancer cell invasion through reconstituted basement membrane compared with serum from saline controls. This was associated with decreased circulating matrix metalloproteinase 9 (MMP‐9) and increased circulating tissue inhibitor of metalloproteinase 1 (TIMP‐1) and TIMP‐3/4 as assessed by zymography and reverse zymography. By using quantitative RT‐PCR, we confirmed morphine‐induced alterations in MMP‐9 and TIMP expression and identified organs, including the liver and spleen, in which these changes originated. Pharmacologic inhibition of MMP‐9 abrogated the difference in chemotactic attraction between serum from saline‐treated and morphine‐treated mice, which indicated that reduced proteolytic ability mediated the decreased migration toward serum from morphine‐treated mice. This novel mechanism may enable morphine administration to promote an environment that is less conducive to tumor growth, invasion, and metastasis.—Xie, N., Khabbazi, S., Nassar, Z. D., Gregory, K., Vithanage, T., Anand‐Apte, B., Cabot, P. J., Sturgess, D., Shaw, P. N., Parat, M.‐O. Morphine alters the circulating proteolytic profile in mice: functional consequences on cellular migration and invasion. FASEB J. 31, 5208–5216 (2017). www.fasebj.org